Autofictional discourse analysis in teenagers: subjectivity through diary - Franco González, Verónica (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
The present study offers the key to understand the teenagers’ diary discourse by the analysis of the available lexicon that they use in their diary writing. Based on the observation of the connotation of those words, we can infer pertinent conclusions about the consideration of the first-person narrator related to their subjectivity; that is, regarding their personality, self-concept or mood, issues intimately bound to the personal development of adolescence.
Keywords: Key words: discourse analysis, adolescence, diary, subjectivity.